Long-term variability of urinary salt excretion and blood pressure in hypertensive patients - Sakaki, Minako; Tsuchihashi, Takuya; Arakawa, Kimika; Fukui, Hiroko; Kameda, Wakako; Tominaga, Mitsuhiro (Hypertension research, 2014)
We investigated the long-term trend and variability of urinary salt (sodium chloride) excretion in hypertensive patients. Subjects included 186 hypertensive patients (103 women and 83 men, mean age: 58.5±10.5 years) who underwent 10 successful 24-h home urine collections over a mean observation period of 7.7 years. We measured 24-h urinary salt excretion and blood pressure (BP) sequentially at the time of each collection and monitored the long-term trend and variability of urinary salt excretion. BP significantly decreased from 145±16/85±11 mm Hg to 130±12/70±11 mm Hg and was associated with an increased use of antihypertensive drugs. The 24-h urinary salt excretion also decreased from 9.5±3.6 g per day at the first measurement to 8.5±3.2 g per day at the 10th measurement. Urinary salt excretion during the observation period ranged from a minimum value of 5.2±1.8 g per day to a maximum value of 13.4±3.6 g per day with a coefficient of variation of 29.2±8.1%. When subjects were assigned to a low, medium and high salt group based on the tertiles of the first measurement of urinary salt excretion and the tertiles based on the mean value of 10 measurements during the observation period, only 56.2% remained in the same category, suggesting that a single measurement of urinary salt excretion can only predict long-term urinary salt excretion in approximately half of the individuals. In conclusion, urinary salt excretion shows large variability such that a single measurement may not be sufficient to assess salt intake in individuals.